(untitled) (The Research of Medical Science Review, 2025)
Objective: To evaluate the barriers causing undue delay in diagnosis and management of common childhood malignancies in low to middle income country (LMIC). Place and Duration: CMH Rawalpindi, 1 year from Jan 2024 to dec 2024 Methodology: This prospective cross-sectional research was carried out at the child Oncology department CMH Rwp, Pakistan. All children aged 2 months to 18 years confirmed with any type of malignancy were included. Parents were asked about for explanations of interruptions faced in the management path of their kids. Delay in the diagnosis and management was defined as the extra time taken before reaching the diagnosis and starting treatment by the patient and health care facilities after onset of symptoms. Four weeks were counted as a delay for hematological malignancy while 6 weeks were counted as a delay for solid tumors after onset of symptoms. Data was compiled and analyzed using SPSS version 25 Results: The average age of our study group participants was 06 years. 63.9% children were male, 36.1% were female. The most common malignancies diagnosed among the children were leukemia, accounting for 55.8% of cases, followed by lymphoma 12.1%, and renal tumors at 6.6% %. 7.2% of the cohort had not received formal education, while the remaining participants exhibited varying degrees of educational attainment. Nutritional assessments revealed that approximately 45.7% of the children had an intermediate nutritional status, whereas 8.1% were classified as having poor nutritional status. Conclusion: Timeliness of diagnosis and management of childhood cancer is a multifaceted challenge involving various barriers. It needs to be addressed at various levels starting from easy access to basic medical services, socioeconomic challenges and accuracy of diagnostic workup. Screening and education-based program can enhance timeliness of diagnosis.